KAJIAN NILAI NUTRISI LIMBAH PADAT HASIL SAMPING PENGOLAHAN RUMPUT LAUT (Eucheuma cottonii) MELALUI PROSES BIOKONVERSI - Hasanuddin, Asriani; Rusdi, Rusdi (FAPETKAN UNTAD, 2012)
Government program that sets seaweed and results olahanya as commodity resulted in an increase in the amount of waste from processing into carrageenan seaweed cause environmental pollution. By him that, has done research on the nutritional evaluation of the waste and the efforts to improve the nutritional value of the waste that can be used as feed. This study uses bioconversion technology and using Rhizopus oligosporus as an inoculant. The study was conducted in two phases, namely the early stages of an evaluation study of the nutritional value of waste carrageenan and test its ability to grow on medium Rhizopus oligosporus waste. Furthermore, the implementation of the waste carrageenan bioconversion using Rhizopus oligosporus on some level in the medium (w/w). Preliminary results demonstrate that the solid waste seaweed had higher levels of crude protein 2.43%, fat 0.52%, ash content 4.07%, carbohydrates 7.25%, crude fiber 2.48%, 85.73% water, cellulose 23.29% and hemicellulose 16.51%. Furthermore Showed that Rhizopus oligosporus can grow well on media without the addition of carrageenan waste Nutrients. Bioconversion can improve the nutrient content of solid waste seaweed. Bioconversion of waste produced has a moisture content between 73.91 to 75.97%, protein content between 13.27 to 16.78%, fat content between 0.20 to 0,25%, ash content between 18.15 to 20.60%, a pH value between 6.56 to 7.35 while the crude fiber content Obtained between 13.45 to 20.37%. Based on the series of this study, it can be concluded that the solid waste Eucheuma cottonii seaweed can be used as a growing medium of Rhizopus oligosporus and can improve the nutritional content of seaweed waste. Use of inoculum in the medium waste carrageenan is possible until the level of 15% (w/w). Â Key words: Bioconversion, byproducts, seaweed processing, solid waste.